Evaluation of National Health Insurance Program (JKN) Services at Puskesmas PB Selayang II Medan - Br Purba, Lopiga Ananda Carolina; Astuty, Delfriana Ayu; Zin, Nor Azrul Mohd; Ekawan, Triki (Faculty of Mathematics and Natural Sciences (FMIPA), Universitas Negeri Padang, Indonesia, 2023)
Evaluation ofÂ Implementation of National Health Insurance Program Services is an assessment or analysis of the implementation of national health insurance program services Based on Law Number 24 of 2011 concerning the Social Security Administering Body (BPJS), the government has taken steps to establish the National.Â The purpose of this study was to evaluate the services of the National Health Insurance Program (JKN) at PB Selayang II Health Center using qualitative methods. The research method used in this study is a qualitative research method with descriptive analytic research design. The results of study found that the implementation of the JKN program at the PB Selayang II Health Center had gone well. The Puskesmas has provided adequate facilities and health workers to serve JKN participants and there are still several obstacles in implementing the JKN program at the Puskesmas, namely the use of the Mobile JKN application. The regulation given by the Mayor is in the form of a UHC (Universal Health Coverage) program that guarantees access to health services for all people, regardless of ownership or use of BPJS. With the UHC program, PB Selayang II Health Center is committed to providing fair and equitable health services to all people.